Koncepcja bezinteresowności ekonomicznej Talcotta Parsonsa - Wechta, Przemysław (My University, 2019)
The task of the paper is to analyze Talcott Parsons’ concept of economic disinter-estedness, which the classical American sociologist introduced at an early stage of his work. It is aimed at economic orthodoxy, whose permanent foundation is thestill vital figure of homo oeconomicus. The concept of disinterestedness is about crossing the limits of one’s own advantage in economic activities. When justifying the concept, Parsons refers to Alfred Marshall and his concept of a “gentleman of the world of free industry and entrepreneurship” and Max Weber’s concept of the “spirit of capitalism”. According to Parsons, the embodiment of disinterestedness in advanced capitalism should become a specific type of bureaucracy.
Talcott Parsons’ concept of economic disinterestedness
Keywords: bezinteresowność; etyka; biurokracja